Tolerance to Tick-Borne Diseases in Sheep: Highlights of a Twenty-Year Experience in a Mediterranean Environment - Pieragostini, Elisa; Ciani, Elena; Rubino, Giuseppe; Petazzi, Ferruccio (IntechOpen, 2011)
None